Edukasi Kompres Hangat pada Leher untuk Mengurangi Intensitas Nyeri Kepala pada Lansia dengan Hipertensi - Destia Kurniawati; Etika Dewi Cahyaningrum; Maria Ulfah (Yayasan Inspirasi El Burhani, 2026)
Introduction: Hypertension is a major cardiovascular health problem with an increasing prevalence and is a significant risk factor for heart disease, stroke, and kidney disorders. Headache is a common complaint among elderly patients with hypertension. Pain management is generally carried out pharmacologically; however, long-term drug use may cause side effects, thus requiring safe non-pharmacological alternatives such as warm compress therapy. Interviews conducted at the Elderly Posyandu in Karangaren Village indicated that most elderly individuals were not familiar with warm compress techniques as a self-management approach for hypertensive headaches. Objective: This community service activity aimed to improve elderly knowledge regarding the application of warm compresses on the neck to reduce headache intensity due to hypertension. Method: This community service activity was conducted on August 8, 2025, involving 13 elderly individuals with hypertension. The intervention included health education through lectures, interactive discussions, and the use of PowerPoint presentations and leaflets. Evaluation was carried out using pre-test and post-test questionnaires. Result: Before the education, most participants (76.92%) had low knowledge levels. After the intervention, an improvement was observed, with 69.23% of respondents reaching a good knowledge level and no participants remaining in the low category. The education contributed positively to increasing elderly understanding of warm compress therapy as an easy, safe, and independently applicable non-pharmacological intervention. Conclusion: Warm compress education improved elderly knowledge in managing headaches related to hypertension. Continuous education by Posyandu cadres is recommended to support the sustained application of warm compress therapy as part of hypertension management in the elderly.